Code-Switching in Speech of Tundra Yukaghir: Bi- and Multilingual Repetition - S. N. Kurilova (Научный диалог)
The linguistic repertoire of the tundra Yukaghir-Polylinguals in Lower Kolyma, Yakutia, with a population of approximately 400 and fewer than 50 speakers, is represented by the Yukaghir, Chukchi, Even, Yakut, and Russian languages. Their speech can be characterized as mixed, including spontaneous code-switching within and between utterances. Our goal is to provide the first description of one of the common cases of code-switching — repetition. It has been established that pronouns, nouns, verbs, as well as introductory words, propositional-nominal constructions, utterances, and their parts can be duplicated. Noun duplicates in both standard and pidginized forms are the most common. Overall, most duplicates are characterized as Yukaghir-Russian. Cases of trilingual duplication are also found. There are no transitions to Chukchi and Even languages during duplication. Intra- and Interphrase realizations of duplicates with dual directionality from one language to another and / or vice versa are noted. As a result of discourse analysis, social-pragmatic functions performed by duplicates have been identified. New linguistic material, in the form of fragments from dialogues and polylogues, transcripts of which have not been previously published, is introduced into scientific circulation.